Migrasi Suku Batak Toba ke Kota Jambi 1961-2018 - Devi Elisabeth Silaban; Denny Defrianti (Prodi Ilmu Sejarah, Jurusan Sejarah, Seni dan Arkeologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Jambi, bekerja sama dengan Masyarakat Sejarawan Indonesia, Jambi, 2021)
This study aims to determine to the early history of the entry of the Toba Batak tribe to the city of Jambi from 1961-2018, the development of migration of the Toba Batak tribe in the city of Jambi from 1961-2018, and how the impact of the migration of the Toba Batak tribe to the city of Jambi 1961-2018. This research is a historical research which consist of four stages, namely heuristic (finding and gathering information relevant to the research). In data collection, researches conducted field research by observing, interviewing, and conducting library research by collecting books, documents, articles, and the like of it. Second, verification (sources critism), examining whether the sources is genuine, both in form and in content. Third, interpretation (interpreting or giving meaning to the facts or historical evidence. The las step is historiography (writing history). The background of the Toba Batak tribe to migrate to the city of Jambi is to change fortunes to the better. Toba Batak tribe is a tribe that has a strong culture of migrating. In the area of origin, the agricultur area is very limited and less fertile. As a result, to develop yourself is even more difficult. In the city of Jambi, the Toba Batak tribe still voiced 3H (Hamoraon, Hagabeon, dan Hasangapon). And 3H becomes their capital to migrate to the city of Jambi.